Comparision of power loss of three-phase induction motor of four techniques with PWM inverter supply - Tadsuan, S.; Suechoey, B.; Saelee, V.; Chompoo-Inwai, C. (My University, 2007)
The purpose of this research is to study the power loss in three-phase induction motors linked with a three-phase PWM inverter by adjusting various fundamental wave voltages of the motors. The experimental procedures used four adjustment techniques as: 1. Constant DC link voltage inverter and adjusting the modulation amplitude 2. Constant modulation amplitude equal 1 and adjusting DC link voltage of inverter 3. Sixstep inverter and 4. Constant modulation amplitude equal 2.3 (over mod land adjusting DC link voltage of inverter. The four techniques were used to adjust V/f-type fundamental waves. The results indicated that the adjustment technique showing the power input, power output, power loss and efficiency of the motor. © 2007 RPS.
Keywords: Harmonic; Over modulation; Power loss; PWM Inverter; Six Step